Solve for b
b=-3
b=-21
Share
Copied to clipboard
b^{2}+24b+144=81
Use binomial theorem \left(a+b\right)^{2}=a^{2}+2ab+b^{2} to expand \left(b+12\right)^{2}.
b^{2}+24b+144-81=0
Subtract 81 from both sides.
b^{2}+24b+63=0
Subtract 81 from 144 to get 63.
a+b=24 ab=63
To solve the equation, factor b^{2}+24b+63 using formula b^{2}+\left(a+b\right)b+ab=\left(b+a\right)\left(b+b\right). To find a and b, set up a system to be solved.
1,63 3,21 7,9
Since ab is positive, a and b have the same sign. Since a+b is positive, a and b are both positive. List all such integer pairs that give product 63.
1+63=64 3+21=24 7+9=16
Calculate the sum for each pair.
a=3 b=21
The solution is the pair that gives sum 24.
\left(b+3\right)\left(b+21\right)
Rewrite factored expression \left(b+a\right)\left(b+b\right) using the obtained values.
b=-3 b=-21
To find equation solutions, solve b+3=0 and b+21=0.
b^{2}+24b+144=81
Use binomial theorem \left(a+b\right)^{2}=a^{2}+2ab+b^{2} to expand \left(b+12\right)^{2}.
b^{2}+24b+144-81=0
Subtract 81 from both sides.
b^{2}+24b+63=0
Subtract 81 from 144 to get 63.
a+b=24 ab=1\times 63=63
To solve the equation, factor the left hand side by grouping. First, left hand side needs to be rewritten as b^{2}+ab+bb+63. To find a and b, set up a system to be solved.
1,63 3,21 7,9
Since ab is positive, a and b have the same sign. Since a+b is positive, a and b are both positive. List all such integer pairs that give product 63.
1+63=64 3+21=24 7+9=16
Calculate the sum for each pair.
a=3 b=21
The solution is the pair that gives sum 24.
\left(b^{2}+3b\right)+\left(21b+63\right)
Rewrite b^{2}+24b+63 as \left(b^{2}+3b\right)+\left(21b+63\right).
b\left(b+3\right)+21\left(b+3\right)
Factor out b in the first and 21 in the second group.
\left(b+3\right)\left(b+21\right)
Factor out common term b+3 by using distributive property.
b=-3 b=-21
To find equation solutions, solve b+3=0 and b+21=0.
b^{2}+24b+144=81
Use binomial theorem \left(a+b\right)^{2}=a^{2}+2ab+b^{2} to expand \left(b+12\right)^{2}.
b^{2}+24b+144-81=0
Subtract 81 from both sides.
b^{2}+24b+63=0
Subtract 81 from 144 to get 63.
b=\frac{-24±\sqrt{24^{2}-4\times 63}}{2}
This equation is in standard form: ax^{2}+bx+c=0. Substitute 1 for a, 24 for b, and 63 for c in the quadratic formula, \frac{-b±\sqrt{b^{2}-4ac}}{2a}.
b=\frac{-24±\sqrt{576-4\times 63}}{2}
Square 24.
b=\frac{-24±\sqrt{576-252}}{2}
Multiply -4 times 63.
b=\frac{-24±\sqrt{324}}{2}
Add 576 to -252.
b=\frac{-24±18}{2}
Take the square root of 324.
b=-\frac{6}{2}
Now solve the equation b=\frac{-24±18}{2} when ± is plus. Add -24 to 18.
b=-3
Divide -6 by 2.
b=-\frac{42}{2}
Now solve the equation b=\frac{-24±18}{2} when ± is minus. Subtract 18 from -24.
b=-21
Divide -42 by 2.
b=-3 b=-21
The equation is now solved.
\sqrt{\left(b+12\right)^{2}}=\sqrt{81}
Take the square root of both sides of the equation.
b+12=9 b+12=-9
Simplify.
b=-3 b=-21
Subtract 12 from both sides of the equation.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}